Assessing the Pavement Quality of National Roads in Sudan - Zumrawi, Magdi M. E. (University of Khartoum Engineering Journal, 2021)
Roads play a vital role in the sustainable economic development for many countries in the world. The quality of road pavement is considered to be one of the most important indicator of economic competitiveness. Therefore, it is very important for Sudan government and road authorities to maintain road networks with appropriate levels of quality and safety standards. The research conducted a field survey in four major national roads to collect data on surface distresses, determine the level of road quality, and identify the most important factors leading to road deterioration. The results obtained showed that 49.5% of the roads are in good condition, 24.4% are in fair condition, and 16.1% are in poor condition and the major distresses observed on roads’ surfaces are cracking and potholes failures. It was found that the main reasons for road deterioration are traffic overloading and climatic changes. Finally, recommendations are provided to help the government and road authorities in Sudan to improve the quality of road network.